Navigating electives: Perspectives from phase III MBBS students and faculty in program evaluation - Sujatha Karjigi; Shyamala KK; Divya Gupta; Karthik R (Asian Journal of Medical Sciences, 2025)
Background: An elective is a learning experience created in the competency-based medical education curriculum to provide an opportunity for the learner to explore, discover, and experience areas or streams of interest in the profession. To implement a program successfully, we need to continuously evaluate the program and make necessary revisions based on feedback, outcomes, and challenges faced. Aims and Objectives: To assess perceptions and challenges faced by students and teaching faculty to provide insights about the best approach to implement electives. Materials and Methods: A cross-sectional survey in which qualitative data on perceptions of electives were collected through an online survey by a validated semi-structured questionnaire with open-ended questions. Analyzed using a 5-point Likert scale. Results: Out of 240 students and 55 preceptors/teaching faculty, most students strongly agreed they could select an elective topic of their interest (96%) and found elective topics highly engaging and relevant to their interests and career goals (42.1%). About 12% of students agreed that topics were assigned to them without their input, and 50% felt topics should have been more innovative. The majority of the students were assessed during the course (84%). The majority of teaching faculty (90%) highly valued the introduction of an elective module and the need for more innovative topics, and 36% agreed that logbook entries, documentation, and evaluation were not completed due to time constraints. Thematic Analysis of Focus Group Discussion with students and teaching faculty revealed many perspectives in their own words. Conclusion: The elective curriculum received positive feedback from participants suggestive of including super-specialty topics, collaborating with external institutions, increasing resource faculty, using electronic logbooks and e-assessments to ease the workload, and finally conducting pre-departure orientations for clarity. Strategic policy changes are essential for better curriculum design and implementation.